NAVIGATING EMOTIONAL REACTIONS TO COVID-19: AN IN-DEPTH ANALYSIS - Silva, Lucas Martins (International Research Journal of Sociology, Psychology and Anthropology, 2024)
The COVID-19 pandemic, which emerged in late 2019, has had profound global impacts, with significant mortality rates reported in various countries. Health care providers and frontline workers are at increased risk of infection due to direct contact with patients, necessitating strict precautions, including the use of personal protective equipment (PPE). These measures have extended to the general population, causing social discomfort and stress. This study examines the emotional responses and psychological impacts of COVID-19, highlighting the challenges faced by individuals in adhering to protective measures and the associated stress.